Secure Authentication Methods for Preventing Jamming Attacks In Wireless Networks (International Journal of Engineering and Computer Science, 2017)
The open nature of the wireless average greeneries it susceptible to intended interfering attacks, typically referred to as blocking. This intended interfering with wireless transmissions can be used as a Launch pad for rising Denial-of-Service attacks on wireless networks. Typically, blocking has been addressed under an external threat model. However, adversaries with internal knowledge of protocol specifications and network secrets can launch low-effort blocking attacks that are difficult to detect and counter. In this work, we address the problem of selective blocking attacks in wireless networks. In these attacks, the adversary is active only for a short period of time, selectively directing messages of high importance. We illustrate the advantages of selective blocking in terms of network performance reduction and adversary effort by presenting two case studies; a selective attack on TCP and one on routing. We show that selective blocking attacks can be launched by performing real-time packet classification at the physical layer. To lessen these attacks, we develop three schemes that prevent real-time packet classification by combining cryptographic primitives with physical-layer attributes. We analyze the security of our methods and evaluate their computational and message overhead